ANALISIS KUALITAS LAYANAN APLIKASI BERKAS MLAKU DHEWE TIPE B DI KECAMATAN SUKODONO - Riyanita Sukowati; Budi Rianto; Sasmito Jati Utama (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
Sukodono district is one of the sub-districts in Sidoarjo Regency that has first tried to become a pioneer of internet-based service providers through service innovations File Mlaku dheWe (BMW). The fact shows that the quality of application services is such an important issue given the technical aspects of its implementation. This study aims to analyze the quality of administrative services and the factors that influence the quality of administrative services based on E-Government, especially in the BMW type B application service in Sukodono District. This research uses descriptive quantitative research methods. The population of this study took 21 respondents. This analysis uses the e-GovQual dimensional approach. The analysis technique of this research uses the Importance Performance Analysis (IPA) method and data processing techniques. The results show (1) The analysis conducted by the researcher using Importance Performance Analysis (IPA) shows that of the 35 sub-indicators studied, the quadrant A variable consists of 11 sub-indicators, quadrant B consists of 7 sub-indicators, quadrant C consists of 9 sub-indicator, and quadrant D consists of 8 sub indicators. (2) The results of the analysis of the quality of administrative services based on E-Government on the Mlakau dheWe file application service type B in Sukodono District, Sidoarjo Regency are well implemented.